Strategi Pembudayaan Technopreneur Menuju Madrasah Hebat di MAN 2 Kulon Progo - Anita Isdarmini (Jurnal Pendidikan Madrasah, 2019)
This Best Practice aims to describe the implementation of Madrasah Technopreneur so that it is able to save MAN 2 Kulon Progo. This innovation is backed by the challenges of Madrasah that must be faced namely the low education and economic parents of the students of MAN 2 Kulon Progo, and graduates of Madrasah who choose to work. The strategic step in making Madrasah Technopreneur is to build a joint commitment of stakeholders, revitalization, compose academic script, launch tagline "MANDAKU SIAP", review of legal umbrella, curriculum preparation, revitalization of infrastructure, Management structure, national level skills Madrasah, internship program, MoU, HR Quality Development, production Unit establishment, development of other outputs and evaluation. The result of innovation from the establishment of Madrasah Technopreneur is growing pride in students as well as teachers and employees of Madrasah, loving madrasah and increasing the spirit to always achieve both academic and non academic. This Best practice also positively impacts the results of acceptance of new learners that are increasing year after year. Graduates of Madrasah are also recognized to possess the competence and expertise of technopreneur, madrasah cooperation with industrial institutions, and madrasah to be the Madrasah referral for the national Madrasah.